Ferulic Acid: A Promising Therapeutic Phytochemical and Recent Patents Advances - Chaudhary, Ashun; Jaswal, Vivek S.; Choudhary, Sonika; Sonika; Sharma, Ajay; Beniwal, Vikas; Tuli, Hardeep S.; Sharma, Sanjeev (Recent Patents on Inflammation & Allergy Drug Discovery, 2019)
Background: Among the various phenolics metabolites, ferulic acid is considered as the promising mitigating, restorative and antioxidant agent. Ferulic acid is one of the most commonly found natural products in vegetables, for example, tomatoes, sweet corn, and in rice grain. Phytochemicals are utilized in the treatment of human ailments and these are derived from the dietary compounds. Objective: The present review widely argued the calming restorative capability of ferulic acid alongside the scientific evidences and its proposed mechanism for activity. Furthermore, we provided the main practical points for the use of ferulic acid in oxidative damages during various diseases. Additionally, the relevant patents on ferulic acid with various therapeutic potential has been discussed. Methods: The approach consisted of searching several resources, including theses, technical reports, web-based scientific databases such as publications on PubMed, ScienceDirect, Springer, PROTA, Google Scholar, and other allied databases. Thus, recent patent regarding the role of ferulic acid therapeutic potenitial has been discussed. Results: One hundred and twenty references have been cited in the present review article. The cited references were found to be suitable and described the therapeutic application of ferulic acid thoroughly. Conclusion: Ferulic acids are known to contrarily down-manage an assortment of extracellular and intrcelullular molecular targets related to infection movement. Various patents on ferulic acid based moieties have been accounted for from 2018. The ferulic acids have a wide scope of impacts against different infections like malignant growth, diabetes, cardiovascular and neurodegenerative diseases. The current review deals with the antioxidant property of ferulic acid and the recent patent describes the role of ferulic acid against human diseases.
Keywords: phytochemicals